A prospective study of the hearing gain achieved in relation to the site and size of tympanic membrane perforation after type 1 tympanoplasty with temporalis fascia graft - Pillai, Gopinathan N.; Reynolds, Anjana Mary; Ayyappankandi, Nazneen Parammal; Ninan, Cyril C. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic otitis media (COM) mucosal type is characterised by recurrent ear discharge and hearing loss secondary to tympanic membrane perforation. Type 1 tympanoplasty is the surgical option for its closure. The objective of this study is to record the site and size of tympanic membrane perforation, quantify the hearing loss with pure tone audiogram and to assess the hearing gain achieved following type 1 tympanoplasty with temporalis fascia graft. Methods: This prospective study comprises 120 patients of the age group of 15 to 60 years with COM who attended the otorhinolaryngology department, from June 2015 to May 2018. Site and size of perforation were assessed by the number of quadrants involved. Hearing loss was quantified by pure tone audiometry (PTA) pre-op and 3, 6 and 12 months post-op. The pure tone average with the air-bone gap (ABG) at 12 months is used for the assessment. Results: In this study, mean pure tone average pre-operatively for small, medium, large and subtotal perforations were 26 dB, 32 dB,35 dB, 42 dB respectively and 14.37 dB, 23 dB, 23.66 dB, and 32.5 dB post operatively after one year. On statistical analysis by ANOVA test, postoperative hearing gain was statistically significant. Conclusions: The study shows that hearing loss was proportional to the size of perforation. Air-bone closure following type 1 tympanoplasty was more for subtotal perforation and for perforations involving both anterior and posterior quadrants.